The need for standard protocols in bioregionalisation: Comments on “The spectre of biogeographical regionalization” by Morrone (2018) - Ung, Visotheary (Zootaxa, 2018)
Morrone (2018) provided a general protocol to undertake biogeographical regionalizations consisting in seven steps, namely 1. defining the study area, 2. assembling distributional data, 3. identifying natural areas, 4. discovering area relationships, 5. defining boundaries/transition zones, 6. regionalization and, 7. area nomenclature. This protocol is aimed at facilitating communication between cross-domain researchers and contributing to the development of a truly integrative biogeography. Here I would like to discuss some ideas raised by Morrone (2018) and show that comparative biogeographical methods (sensu Parenti and Ebach 2009) are based on a cladistic rationale which provides the ontological framework to address this issue i.e. initiate biogeographical regionalizations leading to an integrative biogeography. This kind of standardisation has already been used in different context of biogeographical analysis and highlighted interesting results (Hoagstrom et al., 2014; Ung et al., 2016, 2017).